Editorial Foreword: Is State Still Matters? (Global Focus, 2021)
There are 6 (six) articles for the opening edition of JGF Vol. 1 No. 1. Each article contributes to international relations studies debate, whether the state is still the only and the primary actor or already disaggregated. Globalization has already given numerous challenges and changes to global politics. The authority of the state was multiplicated to the various actor and agendas. Undoubtedly, transnational issues are rising into the field of international relations studies.